2021
DOI: 10.35118/apjmbb.2021.029.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Isolation screening and molecular characterization of zinc solubilizing bacteria and their effect on the growth of wheat (Triticum aestivum)

Abstract: Wheat (Triticum aestivum) is a major cereal crop grown worldwide. Most of the world population depends on wheat for their nutrient requirement. Zinc (Zn) is one of the most crucial elements required for the development of wheat plant. It is one of the micronutrients required in many biochemical cycles. It has been found that the concentration of Zn is below the required level in the soil and hence it remains deficient in the crops. To ameliorate the deficit, chemical fertilizers are added in the soil, where as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Additionally, the isolates were assessed for exopolysaccharide (EPS) production, which supports efficient root colonization and nutrient absorption. Prior research has demonstrated that ZSB isolates capable of producing EPS have been used to enrich crops with zinc (Nandal and Solanki, 2021) [11] . Lastly, the isolates displayed characteristics conducive to plant growth, including ammonia production, a well-documented trait of plant growth-promoting bacteria (Roshni et al, 2020) [15] .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the isolates were assessed for exopolysaccharide (EPS) production, which supports efficient root colonization and nutrient absorption. Prior research has demonstrated that ZSB isolates capable of producing EPS have been used to enrich crops with zinc (Nandal and Solanki, 2021) [11] . Lastly, the isolates displayed characteristics conducive to plant growth, including ammonia production, a well-documented trait of plant growth-promoting bacteria (Roshni et al, 2020) [15] .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this isolate also demonstrated chitinase and phosphatase activity. 33 Under electron microscopy, the colonization of bacteria on PS-MP particles was visualized. The biolm complex consisted of bacterial cells and EPS layer bound to the microplastics.…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial IHK-3 and IHK-25 also produce siderophores, HCN and ammonia. In an investigation, Bacillus tropicus ZA1 was isolated from rhizospheric region and it was able to solubilizes inorganic phosphate, produce IAA and siderophores ( Nandal and Solanki 2021 ). Jaya et al.…”
Section: Discussionmentioning
confidence: 99%